Oestradiol Alters Central 5‐HT1A Receptor Binding Potential Differences Related to Psychosocial Stress but not Differences Related to 5‐HTTLPR Genotype in Female Rhesus Monkeys. (February 2014) - Michopoulos, V.; Perez Diaz, M.; Embree, M.; Reding, K.; Votaw, J. R.; Mun, J.; Voll, R. J.; Goodman, M. M.; Wilson, M.; Sanchez, M.; Toufexis, D.
<x xml:space="preserve">Abstract</x> Social subordination in female macaques represents a well‐described model of chronic psychosocial stress. Additionally, a length polymorphism (5‐HTTLPR) in the regulatory region of the serotonin (5‐HT) transporter (5‐HTT) gene (SLC6A4) is present in rhesus macaques, which has been linked to adverse outcomes similar to that described in humans with an analogous 5‐HTTLPR polymorphism. The present study determined the effects of social status and the 5‐HTTLPR genotype on 5‐HT1A receptor binding potential (5‐HT1A BPND) in brain regions implicated in emotional regulation and stress reactivity in ovariectomised female monkeys, and then assessed how these effects were altered by 17β‐oestradiol (E2) treatment. Areas analysed included the prefrontal cortex [anterior cingulate (ACC); medial prefrontal cortex (mPFC); dorsolateral prefrontal cortex; orbitofrontal prefrontal cortex], amygdala, hippocampus, hypothalamus and raphe nucleui. Positron emission tomography using p‐[18F]MPPF was performed to determine the levels of 5‐HT1A BPND under a non‐E2 and a 3‐week E2 treatment condition. The short variant (s‐variant) 5‐HTTLPR genotype produced a significant reduction in 5‐HT1A BPND in the mPFC regardless of social status, and subordinate s‐variant females showed a reduction in 5‐HT1A BPND within the ACC. Both these effects of 5‐HTTLPR were unaffected by E2. Additionally, E2 reduced 5‐HT1A BPND in the dorsal raphe of all females irrespective of psychosocial stress or 5‐HTTLPR genotype. Hippocampal 5‐HT1A BPND was attenuated in subordinate females regardless of 5‐HTTLPR genotype during the non‐E2 condition, an effect that was normalised with E2. Similarly, 5‐HT1A BPND in the hypothalamus was significantly lower in subordinate females regardless of 5‐HTTLPR genotype, an effect reversed with E2. Taken together, the data indicate that the effect of E2 on modulation of central 5HT1A BPND may only occur in brain regions that show no 5‐HTTLPR genotype‐linked control of 5‐HT1A binding.